RETRACTED: Organizational and technological solutions for planning the construction of buildings of social nature - Zilberova Inna; Fedorovskaya Albina; Novoselova Irina; Petrov Konstantin; Mazanov Nikita (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001